Antitumoral ans inmunomodulatory role for histamine in breast cancer - Nicoud, Melisa Beatriz (2019)
It is well known that histamine is a key regulator of inmune cell functions and it also modulates cancer cell proliferation. The aim of this work was to investigate the effect of histamine and its H4 receptor (H4R) agonist (JNJ28610244) on tumour growth and in the inmune tumour microenvironment as a whole, in a triple negative breast cancer (TNBC) syngeneic model developed in inmunocompetent mice. Tumours of tne TNBC cell line 4T1 were established in Balb/c mice. Treatments employed: histamine (1 or 5mg/kg) and JNJ28610244 (1 or 5mg kg). Results show that histamine treatment (5mg/kg) reduces tumour growth more effectively that JNJ28610244. Histamine but the agonist increases tumour apoptosis and it reduces the number of intratumoural vessels. Histamine also reduces immunosuppression throught the modulation of the tumour microenvironment, as it increasesthe tumour secretion of IFN gamma and reduces the number of T regulatory (Treg) lymphocytes in lymph nodes and spleen. A lower concretation (1mg/kg) of JNJ28610244 reduces tumour size while no inmunomodulatory effects are observed in the immune cell subsets studied. In contrast, a higher concentration (5mg/kg) is not able to decrease tumour growth probably because of the immunosuppressive effect produced in the tumour microenvironment, showing increased levels of interleukin (IL)-10 and decreased levels of IFNy in tumours and increased infiltrating Treg cells in tumour draining lymph nodes. These results highlight the critical interplay between tumour cells and host immune response that determine the clinical therapeutic outcomes and suggest that histamine is a key pleiotropic mediator with therapeutic benefits in TNBC.